Heavy metal ion resistance and bioremediation capacities of bacterial strains isolated from an Antimony Mine. - Sekhula, Koena Sinah (My University, 2005)
Six aerobic bacterial strains [GM 10(1), GM 10 (2), GM 14, GM 15, GM 16 and GM 17] were isolated from an antimony mine in South Africa. Heavy-metal resistance and biosorptive capacities of the isolates were studied. Three of the isolates (GM 15, GM 16 and GM 17) showed different degrees of resistance to antimony and arsenic oxyanions in TYG media. The most resistant isolate GM 16 showed 90 % resistance, followed by GM 17 showing 60 % resistance and GM 15 was least resistant showing 58 % resistance to 80 mM arsenate (AsO4 3-). GM 15 also showed 90 % resistance whereas isolates GM 16 and GM 17 showed 80 % and 45 % resistance respectively to 20 mM antimonate (SbO4 3-). Arsenite (AsO2 -) was the most toxic oxyanion to all the isolates. Media composition influenced the degrees of resistance of the isolates to some divalent metal ions (Zn2+, Ni2+, Co2+, Cu2+ and Cd2+). Higher resistances were found in MH than in TYG media. All the isolates could tolerate up to 5 mM of the divalent metal ions in MH media, but in TYG media, they could only survive at concentrations below 1 mM. Also, from the toxicity studies, high MICs were observed in MH media than TRIS-buffered mineral salt media. Zn2+ was the most tolerated metal by all the isolates while Co2+ was toxic to the isolates. The biosorptive capacities of the isolates were studied in MH medium containing different concentrations of the metal ions, and the residual metal ions were determined using atomic absorption spectroscopy. GM 16 was effective in the removal of Cu2+ and Cd2+ from the contaminated medium. It was capable of removing 65 % of Cu2+ and 48 % of Cd2+ when the initial concentrations were 100 mg/l, whereas GM 15 was found to be effective in the biosorption of Ni2+ from the aqueous solutions. It was capable of removing 44 % of Ni2+ when the initial concentration was 50 mg/l. GM 17 could only remove 20 % of Cu2+ or Cd2+. These observations indicated that GM 16 could be used for bioremediation of xvi Cu2+ and Cd2+ ions from Cu2+ and Cd2+-contaminated aqueous environment, whereas GM 15 could be used for bioremediation of Ni2+.
Thesis (M.Sc.) -- University of Limpopo, 2005
Keywords: Heavy metals; Heavy metals -- Environmental aspects; Heavy metals -- Toxicology